Quantifying the Effects of Different Treadmill Training Speeds and Durations on the Health of Rat Knee Joints - Jaqueline Lourdes Rios; Kevin Rudi Boldt; James William Mather; Ruth Anne Seerattan; David Arthur Hart; Walter Herzog (SpringerOpen, 2018)
Abstract Background Walking and running provide cyclical loading to the knee which is thought essential for joint health within a physiological window. However, exercising outside the physiological window, e.g. excessive cyclical loading, may produce loading conditions that could be detrimental to joint health and lead to injury and, ultimately, osteoarthritis. The purpose of this study was to assess the effects of a stepwise increase in speed and duration of treadmill training on knee joint integrity and to identify the potential threshold for joint damage. Methods Twenty-four Sprague-Dawley rats were randomized into four groups: no exercise, moderate duration, high duration, and extra high duration treadmill exercise. The treadmill training consisted of a 12-week progressive program. Following the intervention period, histologic serial sections of the left knee were graded using a modified Mankin Histology Scoring System. Mechanical testing of the tibial plateau cartilage and RT-qPCR analysis of mRNA from the fat pad, patellar tendon, and synovium were performed for the right knee. Kruskal-Wallis testing was used to assess differences between groups for all variables. Results There were no differences in cartilage integrity or mechanical properties between groups and no differences in mRNA from the fat pad and patellar tendon. However, COX-2 mRNA levels in the synovium were lower for all animals in the exercise intervention groups compared to those in the no exercise group. Conclusions Therefore, these exercise protocols did not exceed the joint physiological window and can likely be used safely in aerobic exercise intervention studies without affecting knee joint health.